Aggressive giant cell tumour of the talus: a rare case report and challenges faced during its management - Singh, Abhishek; Bora, Shradha; J. K., Giriraj; Menon, Gopinath (International Journal of Research in Orthopaedics, 2022)
Giant cell tumour (GCT) of the bone is a locally aggressive benign tumour that commonly occurs in the epiphyseal ends of long bones. Its occurrence in the small bones of the foot like the talus is rare. In this case report we described a case of aggressive GCT of the talus (Campanacci grade 3) in a twenty-one years old male diagnosed by the presence of a well-defined osteolytic lesion seen involving the talar body with cortical breach and soft tissue extension confirmed to be a GCT by closed needle biopsy. The patient was managed surgically by excision of the tumour mass in-toto along with the talus followed by tibio-calcaneal fusion using free fibular strut graft and Ilizarov frame. At 3 months follow up no evidence of fusion was seen and therefore secondary augmentation with a cortico-cancellous graft from the iliac crest was done to aid fusion and Ilizarov fixator was removed 6 months after the surgery. The patient at one year follow up had shown no signs of recurrence of the tumour and has a pain free, stable fused tibiocalcaneal joint with a bipedal unassisted gait. Our case report found excision of talus combined with tibio-calcaneal fusion using free fibular strut graft along with cortico cancellous iliac bone graft to have a good outcome in terms of aiding tibio-calcaneal arthrodesis and thereby providing pain relief and providing a stable foot to the patient.